PEMERIKSAAN DAN EDUKASI KESEIMBANGAN DINAMIS PADA KELOMPOK LANSIA KARANG LANSIA RAHAYU BANJAR KERTHA BHUWANA, DENPASAR - I Made Dhita Prianthara; I. A Pascha Paramurthi; Komang Tri Adi Suparwati; Ida Ayu Astiti Suadnyana; I Putu Prisa Jaya; I Putu Astrawan; I Gusti Ayu Sri Wahyuni Novianti; Ida Ayu Ratih Wulansari Manuaba (Universitas Mataram, 2023)
Balance refers to the body's ability to maintain balance while adjusting to gravity, the ground, and other objects in its environment. Balance disorders can reduce the quality of life and reduce the independence of the elderly. Elderly people with balance disorders are at higher risk of falling, which can result in a variety of traumas, including broken bones, serious injuries, and even death. This activity aims to examine and provide education to the elderly regarding balance and various kinds of risks caused by balance disorders as well as preventive measures that can be carried out in the form of balance exercises. The method used in this activity is divided into several stages, namely the licensing and audience stages with the elderly, then the implementation stage of the activity by carrying out a balance check using the Fukuda step test. The next stage is to provide education about balance and preventive measures that can be taken to prevent balance disorders. The output of this activity is an increase in the quality of life of the elderly, while the outcome is the satisfaction of the elderly with the services provided. The results of this community service activity were the number of elderly who participated in the activity as many as 26 people with details of men totaling 8 (30.8%) people, while women totaling 18 (69.2%) people. There were 17 (65.4%) elderly who experienced balance disorders and 9 (34.6%) people with good balance. Based on these results, it can be concluded that many elderly people experience balance disorders in the Karang Lansia Rahayu Elderly Group, Banjar Kertha Bhuwana, Denpasar.